Image of the Educator: (re)Thinking Identity - Maclean, Veronica (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2024)
This paper tells of an early childhood educator’s search for meaning making while experiencing a crisis of the self—a deep questioning of personhood, worthiness, ability, and purpose. It represents a snapshot of a particular time in a particular life at the convergence of a master’s program in ECE, a worldwide pandemic, and a provincial research project, which culminated in personal crisis and a great unsettling of identity. It is written in first person, from the ‘I’—the author’s humancentric appraisal of a personal pedagogical intervention, a reckoning with the self—in the hope of finding something otherwise, and something more generative as an educator within early childhood education. The paper grapples with the question of how we can create the conditions for early childhood educators to “read hard, think hard and write hard”—to dig deep, and to go deeper (St. Pierre, 2019) without dismantling a sense of self or a personhood that embodies a deep desire to contribute positively to our unfinished world.